Effects of modified intake surface to gasoline engine performance with the use of LPG - Ilminnafik, Nasrul; Triono, Agus; Ali, Reynaldi Akbar; Mahmud, Rizal; Prasetiyo, Dani Hari Tunggal (Jurnal Polimesin, 2024)
Indonesia observes a yearly rise in motor vehicle possession. Failure to consider alternate fuels in these trends may result in the depletion of gasoline. Out of the potential alternatives, Liquified Petroleum Gas (LPG) appears to be the most favorable. The sole issue lies in the elevated engine temperature and subsequent decrease in performance caused by its utilization. To address this vulnerability, it is advisable to employ a cooling injection method, such as water injection. Nevertheless, the rise in exhaust emissions linked to water injection highlights the necessity for optimization. This study aims to optimize coolant injection systems by conducting experiments with different modifications, such as conventional intake surfaces, dimple intake surfaces with gaps, and dimple intake surfaces without gaps. The gapless dimple inlet surface demonstrates superior performance in terms of exhaust emissions, power, and torque compared to both conventional inlet surfaces and slotted dimple inlet surfaces